2024
DOI: 10.1051/0004-6361/202348065
|View full text |Cite
|
Sign up to set email alerts
|

Phenomenology and periodicity of radio emission from the stellar system AU Microscopii

S. Bloot,
J. R. Callingham,
H. K. Vedantham
et al.

Abstract: Stellar radio emission can measure a star's magnetic field strength and structure, plasma density, and dynamics, and the stellar wind pressure impinging on exoplanet atmospheres. However, properly interpreting the radio data often requires temporal baselines that cover the rotation of the stars, orbits of their planets, and any longer-term stellar activity cycles. Here we present our monitoring campaign on the young, active M\,dwarf AU\,Microscopii with the Australia Telescope Compact Array between 1.1 and 3.1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 71 publications
0
1
0
Order By: Relevance
“…Already in the eighties of the last century Kahler et al [162] presented radio light curves suspecting a type-IV-like burst associated with a flare. Only recently Bloot et al [163] presented a 250-hour-long investigation of the planet-hosting young and active star AU Mic using the Australia Telescope Compact Array in a frequency band between 1.1 and 3.1 GHz. These authors found a variety of bursts on AU Mic and present a unique classification, but confirm no analogs of solar type-II or type-IV occurrences.…”
Section: Stellar Cmesmentioning
confidence: 99%
“…Already in the eighties of the last century Kahler et al [162] presented radio light curves suspecting a type-IV-like burst associated with a flare. Only recently Bloot et al [163] presented a 250-hour-long investigation of the planet-hosting young and active star AU Mic using the Australia Telescope Compact Array in a frequency band between 1.1 and 3.1 GHz. These authors found a variety of bursts on AU Mic and present a unique classification, but confirm no analogs of solar type-II or type-IV occurrences.…”
Section: Stellar Cmesmentioning
confidence: 99%